DOCUMENTARY FILM AS THE MISSIONARY ENDEAVOR OF DIGITAL ERA - Riki Rikarno (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
One of television shows is the program of documentary film. Documentary film with religious content involving religious thought, religious values, and public figures of a religion has educational values and wisdom made into a description of life. It has the essence of missionary endeavor that has social purpose and function namely producing peaceful, prosperous, happy and safe life. The making of documentary film of missionary endeavor or more often called the production of documentary film of missionary endeavor is the process of film making from the story idea until the production of documentary film of missionary endeavor. In planning a production, a professional producer will be faced on five things that need deep thought namely the material of production, the means of production (equipment), the cost of production (financial), the executive organization of production, and the implementation stage of producing the documentary film of missionary endeavor.